Case Report of Mimicry between Synovial Hemangioma and Synovial Chondromatosis of the Shoulder - Colanese, Justin (J Orthop Case Rep, 2016)
INTRODUCTION: Synovial hemangioma is a developmental hamartoma of vascular tissue within the synovium; no cases involving the shoulder girdle have been described in the literature. Synovial chondromatosis is a benign condition in which synovial cells undergo metaplasia into hyaline cartilage and is also thought to infrequently affect the shoulder region. CASE REPORT: A 44-year-old female presented with left shoulder pain of 7-year duration. Magnetic resonance image displayed a 2.5 cm × 2.5 cm lesion in the anterior glenohumeral joint, with hypointense T1- and hyperintense T2-weighted signal and peripheral and septal enhancement. Arthroscopic biopsy of the synovial-appearing mass led to a histologic diagnosis of synovial hemangioma. Successful embolization was performed, and repeat arthroscopy then revealed a white consolidated mass at the subscapularis recess. After en bloc excision, histologic evaluation was consistent with synovial chondromatosis. At 6 months, she denied any pain or limitation in her shoulder. CONCLUSION: Synovial hemangioma has never before been reported to involve the shoulder region. Histologically, engorged inflammatory vessels secondary to a mass effect are identical to a hemangioma. The clinician should be aware that synovial chondromatosis or other masses may compress synovial vessels and histologically mimic a hemangioma.